REDUCTION OF VECTOR COMPARTEMENT ON DENGUE DISEASE TRANSMISSION MODEL - RANI PUTRI (NIM : 10113002), ALISSA
Dengue hemorrhagic fever or commonly abbreviated as DHF is a disease caused by Dengue virus. The disease is spread by Aedes aegypti mosquitoes. In fact, the dataconcerning Dengue virus carrying mosquitoes is very difficult to observe. Available data related to DHF problems is just data about dengue sufferers. With this fact, a mathematical model is constructed by using daily incidence data to estimate the unknown parameters. The intensity of the spread of the disease will also be measured by an estimate of the basic reproductive ratio during the period of observation. In this final project, the dengue disease transmission model is re-formulated by reducing the mosquito compartment in an S-I-R-Sv-Iv (Susceptible-Infectious- Recover-Susceptible Vector-Infectious Vector) model. The threshold of this model will also be estimated here. The reduced model obtained is a S-I-R (Susceptible- Infectious-Recover) system. The difference with the S-I-R equation system lies in the time-dependent coefficient of infection rate. This coefficient is obtained using shooting method with data of DHF patients for one year. The endemic threshold of this model is estimated using the Basic Reproductive Ratio value of the SIR model. The result of the estimated Basic Reproductive Ratio contains a timedependent coefficient. Therefore, the time-dependent coefficients will be estimated by choosing values that representing data for one year, ie by selecting the largest value or by selecting the expectated value of the distribution coefficient data. In the future, the estimated threshold values can be used to compare the intensity of the dengue transmission from year to year.